12(x+8)=3

Simple and best practice solution for 12(x+8)=3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12(x+8)=3 equation:


12(x+8)=3

We simplify the equation to the form, which is simple to understand
12(x+8)=3

Reorder the terms in parentheses
+(+12x+96)=3

Remove unnecessary parentheses
+12x+96=+3

We move all terms containing x to the left and all other terms to the right.
+12x=+3-96

We simplify left and right side of the equation.
+12x=-93

We divide both sides of the equation by 12 to get x.
x=-7.75

See similar equations:

| w=0.0875t-0.45 | | (4-z)(4z-1)=0 | | 7(y-7)-7=-6(-3y+7)-3y | | 41-18+9=x-4x+81x | | 7-(-4)=4x-14-21x | | -6(x-4)+2=26 | | 4s^3t^3+24s^2t^2=36st | | -4s^3t^3=24s^2t^2 | | (x-1)+(x-17)=42 | | 2x+4=-2x+3 | | p(-2)=30 | | (x-1)+(x-18)=42 | | 6x^3+10x^2=-4x | | cx+c^2=-4x-16 | | 3/2x-7/x=-3 | | 7a^3b^3=63ab^3 | | 5x+8y=-20 | | 10x-4=4x+3 | | f(3)=9 | | 5x+8y=20 | | 0.24=ln(y) | | -3x-5x-3a-5b-2x-6b-6a= | | -n+5n=-4 | | 9/10x5 | | 8+3(x+4)=29 | | 48x^2-12x-90=0 | | 2yx^5=162yx^3 | | -14=8n+6n | | 11x+4=24 | | x=3p+6 | | f(-x)=6x-7 | | -8(1-2m)=88 |

Equations solver categories